Tracking Concept-Based Structures Through Repetitive Text Patterns In The Quran Revealing Possible Ontological Relationships - Nazia Nishat; Rosalina Abdul Salam; Yusuf Mahbubul Islam; Zulkifly Mohd Zaki (Penerbit UMT, Universiti Malaysia Terengganu, 2026)
Indexed by ERA / MYCITE